2001
DOI: 10.1002/1521-4141(200112)31:12<3726::aid-immu3726>3.0.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

Cathepsin S and an asparagine-specific endoprotease dominate the proteolytic processing of human myelin basic proteinin vitro

Abstract: The biochemical characterization of antigen degradation is an important basis for a better understanding of both the immune response and autoimmune diseases mediated by MHC class II molecules.In this study we used high‐performance liquid chromatography and mass spectrometry to analyze the processing of myelin basic protein (MBP), a potential autoantigen implicated in the pathogenesis ofmultiple sclerosis. We resolved the kinetics of MBP processing by lysosomal extracts or purified endocytic proteases, identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
70
0
2

Year Published

2004
2004
2008
2008

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 93 publications
(81 citation statements)
references
References 36 publications
9
70
0
2
Order By: Relevance
“…It is involved in both the intracellular breakdown of li [9] and proteolytic processing of different antigens including myelin basic protein, a potential autoantigen implicated in the pathogenesis of MS [33]. CatS activity is required for induction of the MHC II-mediated collagen-induced arthritis [34].…”
Section: Discussionmentioning
confidence: 99%
“…It is involved in both the intracellular breakdown of li [9] and proteolytic processing of different antigens including myelin basic protein, a potential autoantigen implicated in the pathogenesis of MS [33]. CatS activity is required for induction of the MHC II-mediated collagen-induced arthritis [34].…”
Section: Discussionmentioning
confidence: 99%
“…However, it is possible that loss of processing sites (for AEP or other enzymes) as a result of post-translational protein modifications might enhance the presentation of T cell epitopes in other antigens/autoantigens. This idea is supported by recent evidence that proteolytic processing reactions, for both class I and class II major histocompatibility complex epitopes, can be destructive as well as productive (25)(26)(27)). An example of this, which also illustrates how direct and indirect effects of Asn deamidation on immune recognition can be linked, is seen in the case of another AEP substrate, myelin basic protein (MBP).…”
Section: Discussionmentioning
confidence: 75%
“…An example of this, which also illustrates how direct and indirect effects of Asn deamidation on immune recognition can be linked, is seen in the case of another AEP substrate, myelin basic protein (MBP). A T cell epitope lying between residues 85-99 in MBP is destroyed by AEP cleavage at Asn-94 (25,26). We have shown that presentation of this peptide to MBP-specific T cells is inversely proportional to AEP activity and have suggested that T cells specific for this region of MBP escape tolerization in the thymus because of this destructive processing reaction (26).…”
Section: Discussionmentioning
confidence: 90%
“…The requirement for AEP in tetanus presentation is a robust example of enzyme-restricted Ag processing. Similarly, AEP-mediated processing of MBP has been shown to destroy an asparagine-containing immunodominant epitope, MBP peptide 85-99 (6,19). Because MBP-derived epitopes are presented intrathymically and can contribute to self-tolerance against MBP, the questions of how and whether such peptides are generated are of great importance.…”
Section: Discussionmentioning
confidence: 99%
“…Blockade of the progressive cleavage of Ii results in the accumulation of Ii intermediates and a corresponding decrease in surface expression of class II MHC products (4,5). Experiments using human B cells treated with the cathepsin S (CatS)-specific inhibitor leucine-homophenylalanine-vinyl sulfone (LHVS) (6,7) and characterization of CatS knockout mice (2,8,9) have implicated CatS in the terminal cleavage of Ii to yield CLIP (10). Further studies have demonstrated cell-specific cleavage of p10 by cathepsin L (CatL) (11) in thymic epithelial cells (8) and cathepsin F (CatF) in macrophages (9).…”
mentioning
confidence: 99%